Function of RAD6B and RNF8 in spermatogenesis. Issue 2 (17th January 2018) - Guo, Yingli; Song, Yanfeng; Guo, Zhao; Hu, Mengjin; Liu, Bing; Duan, Hongyu; Wang, Le; Yuan, Tianxia; Wang, Degui
ABSTRACT: Histone ubiquitination regulates sperm formation and is important for nucleosome removal during spermatogenesis. RNF8 is an E3 ubiquitin ligase, and RAD6B is an E2 ubiquitin-conjugating enzyme. Both proteins participate in DNA damage repair processes via histone ubiquitination. Loss of RNF8 or RAD6B can lead to sterility in male mice. However, the specific mechanisms regulating these ubiquitin-mediated processes are unclear. In this study, we found that RNF8 knockout mice were either subfertile or sterile based on the numbers of offspring they produced. We explored the mechanism by which RAD6B and RNF8 knockouts cause infertility in male mice and compared the effects of their loss on spermatogenesis. Our results demonstrate that RAD6B can polyubiquitinate histones H2 A and H2B. In addition, RNF8 was shown to monoubiquitinate histones H2 A and H2B. Furthermore, we observed that absence of histone ubiquitination was not the only reason for infertility. Senescence played a role in intensifying male sterility by affecting the number of germ cells during spermatogenesis. In summary, both histone ubiquitination and senescence play important roles in spermatogenesis.